The 2nd China Vaccinology Integrated Innovation & Teaching Development Conference: Promoting the construction of vaccinology discipline system - Yingqi Chen; Yuelong Shu; Hui Zheng; Caijun Sun; Chuanxi Fu (Human Vaccines & Immunotherapeutics)
The 2nd China Vaccinology Integrated Innovation & Teaching Development Conference was held in Sun Yat-sen University, Shenzhen, 18–19, November 2023. Over 200 participants in the field of Vaccinology gathered together to address challenges and issues relevant to vaccine education and training courses, research, and public health programs in China. The conference themed “Promoting the Integrated and Innovative Development of Vaccinology through Collective Efforts.” The conference was organized by the China Association of Vaccine (CAV) and hosted by Vaccinology Education Professional Committee of CAV, and School of Public Health (Shenzhen), Sun Yat-sen University. Other partners included the Medical Virology Branch of the Chinese Medical Association, the editorial committee of the Chinese Journal of Preventive Medicine, Human Vaccines & Immunotherapeutics, and the People’s Medical Publishing House. The 1st conference was held in Hangzhou, in October 2020.